The Relationship between Inward Foreign Direct Investment, Economic Growth and Carbon Emissions: A Case of Italy from G7 Countries - Nawaz, Farrukh; Sadiq, Misbah; Oudat, Mohammad Salem; Saleem, Khalil Abu; Kayani, Umar; Khan, Mrestyal (International Journal of Energy Economics and Policy, 2024)
Recently, a significant amount of carbon dioxide emissions has grabbed the attention of global community. Thus, this study attempts to investigate the impact of inward foreign direct investment, and economic growth on carbon dioxide emissions in case of Italy. We took Italy as our sample country as it has committed to achieve carbon neutrality by 2050. We took annual time series data for the dependent variable (CO2) and explanatory variables (GDP, FDI, Natural Resources) for the period ranging from 1990 to 2021. To examine the long run relationship between the variables we used autoregressive distributed lags bounds test of cointegration. The empirical findings revealed the existence of long-run relationships among the variables of the model. Furthermore, we also found that natural resources unidirectionally caused CO2 and GDP.